2019
DOI: 10.3844/ojbsci.2019.203.212
|View full text |Cite
|
Sign up to set email alerts
|

The Test of Genotype Adaptation of Several Garlic Varieties on the Highland

Abstract: This study aims to determine the growth patterns of four types of local garlic (Allium sativum L.) and to obtain the adaptive appearance of the agronomical characteristics with maximum tuber weight in two different altitude places. The research was conducted in the Borah garlic farmer garden, Wiyurejo village, Pujon subdistrict, Batu city with an altitude of 1200 m above sea level, daily temperature of 15-20C and average rainfall of 21.400 millimeter/year and in the UB pilot garden of Cangar, Tulungrejo Urban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…It showed that while Lumbu Kuning and Lumbu Putih had increasing diameters of dry bulb in Lembang, Tawangmangu Baru and Lumbu Hijau had decreasing values, and vice versa. These results supported the previous study on the highland of East Java that found the effect of G×L interaction on garlic bulb diameter (Gomes et al, 2019).…”
Section: The Effect Of G× L Interaction On Yield Characterssupporting
confidence: 92%
See 1 more Smart Citation
“…It showed that while Lumbu Kuning and Lumbu Putih had increasing diameters of dry bulb in Lembang, Tawangmangu Baru and Lumbu Hijau had decreasing values, and vice versa. These results supported the previous study on the highland of East Java that found the effect of G×L interaction on garlic bulb diameter (Gomes et al, 2019).…”
Section: The Effect Of G× L Interaction On Yield Characterssupporting
confidence: 92%
“…Although evaluations of those varieties have been done in many locations such as highlands of Malang (Anjani et al, 2019), Bromo (Saidah et al, 2022), Cianjur (Dianawati et al, 2022), Sembalun (Hadiawati et al, 2022), Lembang (Muliani et al, 2023), Dieng (Azmi et al, 2022), Alahan Panjang (Kristina et al, 2023) or lowlands of Muaro Jambi (Kurniaty et al, 2022), however, genetic stability evaluation is rarely reported. Genetic stability is an important factor in breeding evaluations as well as in developing recommendations for farmers in different locations (Obel et al, 2020;Gomes et al, 2019). The study aimed to evaluate agronomic responses of four garlic varieties planted on two different uplands in West Java.…”
Section: Introductionmentioning
confidence: 99%
“…Garlic productivity in Indonesia has been low at around 6.39 ton/ha, while in the world average is 9.73 ton/ha [2]. The low production was due to the smaller size of local garlic bulbs than imported garlic, the diameter of Indonesian garlic bulbs was only 3-5 cm [3][4][5][6][7]. This has caused Indonesian farmers to be reluctant to plant garlic due to losing competition in terms of bulb size and lower selling price of imported garlic [8].…”
Section: Introductionmentioning
confidence: 99%